2018
DOI: 10.1002/jcb.27885
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid–induced survival effects in SH‐SY5Y neuroblastoma cells

Abstract: Neuroblastoma is a malignant childhood cancer arising from the embryonic sympathoadrenal lineage of the neural crest. Retinoic acid (RA) is included in the multimodal therapy of patients with high‐risk neuroblastoma to eliminate minimal residual disease. However, the formation of RA‐resistant cells substantially lowers 5‐year overall survival rates. To examine mechanisms that lead to treatment failure, we chose human SH‐SY5Y cells, which are known to tolerate incubation with RA by activating the survival kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Enrichment of membrane proteins was accomplished using the Plasma Membrane Protein Extraction Kit (Abcam, Berlin, Germany) with 500 ml Homogenize Buffer Mix according to the manufacturer's protocol. Protein quantification and Western blotting were executed according to standard protocols as previously described (Waetzig et al, 2019). Blots were probed with the following antibodies: ABCC2 (c-518048, dilution 1:100; Santa Cruz Biotechnology), GAPDH (sc-47724, dilution 1:5000; Santa Cruz Biotechnology), and anti-mouse (IRDye 800CW 926-32210, dilution 1:10,000; LiCOR, Bad Homburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment of membrane proteins was accomplished using the Plasma Membrane Protein Extraction Kit (Abcam, Berlin, Germany) with 500 ml Homogenize Buffer Mix according to the manufacturer's protocol. Protein quantification and Western blotting were executed according to standard protocols as previously described (Waetzig et al, 2019). Blots were probed with the following antibodies: ABCC2 (c-518048, dilution 1:100; Santa Cruz Biotechnology), GAPDH (sc-47724, dilution 1:5000; Santa Cruz Biotechnology), and anti-mouse (IRDye 800CW 926-32210, dilution 1:10,000; LiCOR, Bad Homburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…Whole cell lysates and immunoblotting. Whole cell lysates and immunoblotting were performed as previously described (17,23,24) Cell adhesion assay. Corning Matrigel basement membrane mix (VWR) was thawed overnight at 4˚C.…”
Section: Genome-wide Expression Analysismentioning
confidence: 99%
“…In addition to the genomic mechanisms, non-genomic mechanisms of RA have been discussed. Studies have reported that RA can activate ERK1/2 kinases ( Bruck et al, 2009 ; Waetzig et al, 2019 ; Cañón et al, 2004 ) which may have a role in cytoskeletal rearrangement and neurite outgrowth ( Pan et al, 2005 ). Also, retinoylation (RA acylation) - a post-translational alteration of proteins by eukaryotic cells ( Das et al, 2014 ) which may have a role in cell differentiation ( Takahashi and Breitman, 1989 ).…”
Section: Atra As a Promising Host Directed Therapy For Tbmentioning
confidence: 99%